Pengaruh H2O2 Dalam Pengolahan Air Payau Menggunakan Metode Koagulasi Dengan PAC dan Alumunium Sulfat - Prabowo, Bambang Hari; Nursaidah, Zahra; Safitri, Febby (Jurnal Teknik: Media Pengembangan Ilmu dan Aplikasi Teknik, 2019)
Brackish water is water caused by intrusion of sea water into fresh water sources, with a composition of salt content between 0.5 - 30 g per Liter. In certain areas often used by residents around the coast as daily necessities, such as bathing, washing clothes and others. Brackish water is still difficult to be processed into fresh water. Therefore, efforts are needed to find alternative methods that can be used for brackish water treatment. This study examines the efficiency of reducing brackish water salinity, and to reduce the value of TDS, TSS, pH, and Turbidity reserves using coagulation with coagulant methods. Variations used for coagulation are the stirring speed of 100 rpm and coagulant doses of 20 ppm, 40 ppm, 60 ppm and 100 ppm. The results obtained on the use of PAC coagulants with a reduction in TDS of 19.94%, TSS of 38.09%, Turbidity of 85.83%, Na levels of 0.64% and Mg levels of 11.61%. While the use of aluminum sulfate coagulant with TDS reduction of 17.59%, TSS 38.74%, Turbidity 85.10%, Mg levels of 53.79% and Na levels of 40.12%, aluminum sulfate coagulants and PAC did not affect the decrease in Cl measure.